2018
DOI: 10.3389/fimmu.2018.02233
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Cellular Dynamics in Cancer and HIV: What Can We Learn for the Follicular CD4 (Tfh) Cells?

Abstract: Lymph nodes (LNs) are central in the generation of adaptive immune responses. Follicular helper CD4 T (Tfh) cells, a highly differentiated CD4 population, provide critical help for the development of antigen-specific B cell responses within the germinal center. Throughout the past decade, numerous studies have revealed the important role of Tfh cells in Human Immunodeficiency Virus (HIV) pathogenesis as well as in the development of neutralizing antibodies post-infection and post-vaccination. It has also been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 178 publications
(240 reference statements)
0
9
0
Order By: Relevance
“…However, we found a decrease in the proportion of MoMDSCs in SN, which might promote T cell immunity through various metabolic effects [ 27 ]. Meanwhile, an increase in Tfh cells in SN could enhance antitumor immunity [ 28 ]. Here, we observed that in SN, M2 macrophages, a type of immunosuppressive cells, were clustered in subcapsular sinus areas of lymph nodes, the main functional area for antigen presentation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we found a decrease in the proportion of MoMDSCs in SN, which might promote T cell immunity through various metabolic effects [ 27 ]. Meanwhile, an increase in Tfh cells in SN could enhance antitumor immunity [ 28 ]. Here, we observed that in SN, M2 macrophages, a type of immunosuppressive cells, were clustered in subcapsular sinus areas of lymph nodes, the main functional area for antigen presentation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased adaptive immune responses are a hallmark of progressive lentiviral infection (27)(28)(29)(30)(31)(32)(33). Although the underlying mechanisms are multifactorial, preferential HIV/SIV infection of follicle-resident CD4 ϩ Tfh cells (reviewed in reference 65), loss of pathogen-specific memory CD4 ϩ T cells (66,67), exhaustion of adaptive lymphocytes (68,69), and aberrant inflammation (70) are all described contributors.…”
Section: Discussionmentioning
confidence: 99%
“…Tfh cells are an important reservoir for HIV/SIV (27)(28)(29)(30)(31)(32)(33), and their predicted infection by SIV in our coinfection model may compromise the generation of ZIKV antibodies. A combination of Tfh loss and ISG-mediated hypoantigenemia may be cumulatively operative in decreasing ZIKV-specific NAbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In NK cells from HIV infected individuals, expression of TIGIT is correlated with disease progression and NK cell dysfunction (160). Although the role of TIGIT is not well-defined in HIV infection, TIGIT ligands such as PVR are increased by CD4 T FH cells in lymph nodes from HIV infected patients compared to heathy donors suggesting it may play a role in viral persistence (161).…”
Section: Tigit Expression In Hiv Infectionmentioning
confidence: 99%